2005
DOI: 10.1049/ip-opt:20045068
|View full text |Cite
|
Sign up to set email alerts
|

High speed (>13 GHz) modulation of 850 nm vertical cavity surface emitting lasers (VCSELs) with tapered oxide confined layer

Abstract: Improved oxide-implanted VCSELs utilising the tapered oxide layer are presented. The VCSELs exhibited similar static performance, but superior modulation bandwidth up to 13.2 GHz, compared with conventional blunt oxide VCSELs. The damping rate was reduced two times in the tapered oxide VCSEL and therefore enhanced the maximal modulation bandwidth. A very clean eye was demonstrated from the improved VCSEL with a rising time of 26 ps, falling time of 40 ps and jitter of less than 20 ps, operating at 10 Gbit/s wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This value is comparable with the value of 6.5 GHz/√mA obtained by Chang et al [24]. (iii) K-factor: For analog modulation applications of a single-mode VCSEL a low value of K-factor is beneficial [21].…”
Section: (Ii) Modulation Current Efficiency Factor (Mcef)supporting
confidence: 84%
“…This value is comparable with the value of 6.5 GHz/√mA obtained by Chang et al [24]. (iii) K-factor: For analog modulation applications of a single-mode VCSEL a low value of K-factor is beneficial [21].…”
Section: (Ii) Modulation Current Efficiency Factor (Mcef)supporting
confidence: 84%
“…To decrease the parasitic capacitance, the multiple oxide layer was proposed to replace the single oxide layer because the device capacitance is inversely proportional to the oxide layer thickness [5][6][7] . Figure 3 shows the simulated frequency responses of the VCSEL with the singleand double-confined oxide layers.…”
Section: Design Of the High-speed 850-nm Vcselmentioning
confidence: 99%
“…where R m , C T , R loss (f ) and C pad (f ) represent mirror total series resistance (R n + R p ), combined mesa capacitance (C j + C jo + C m ), polyimide dielectric loss and pad capacitance, respectively. In previously reported VCSEL circuit models used for parasitic parameter extraction [14,18,32], the frequency dependence of the material dielectric permittivity (ε r ) and R loss was ignored, and thus fixed values for C pad and R loss were used. Based on a study reported by the author and collaborators in [33], the functional dependence of ε r and R loss on frequency, which was approximated by a Gaussian function with fitting parameters, is included in the model presented here:…”
Section: Equivalent Circuit Analysis and Parameter Extractionmentioning
confidence: 99%
“…Measured and fitted data at other bias currents and for the 12 μm devices were omitted for clarity. The convergence of the fitting values to reasonable values was enhanced by assigning a range of initial values for R m , R LF , C p , C T and R d based on either previously reported values for similar structure and size or estimations from simple geometrical considerations [14,18,31,32]. Finally, all the circuit parameters were allowed to vary about these values to minimize the error.…”
Section: Equivalent Circuit Analysis and Parameter Extractionmentioning
confidence: 99%